C–H functionalisation of aldehydes using light generated, non-stabilised diazo compounds in flow. Issue 83 (11th September 2018) - Dingwall, Paul; Greb, Andreas; Crespin, Lorène N. S.; Labes, Ricardo; Musio, Biagia; Poh, Jian-Siang; Pasau, Patrick; Blakemore, David C.; Ley, Steven V.
Abstract : Here we explore further the use of oxadiazolines, non-stabilised diazo precursors which are bench stable, in direct, non-catalytic, aldehyde C–H functionalisation reactions under UV photolysis in flow and free from additives. Abstract : The difficulty in accessing and safely utilising non-stabilised diazo species has in the past limited the application of this class of compounds. Here we explore further the use of oxadiazolines, non-stabilised diazo precursors which are bench stable, in direct, non-catalytic, aldehyde C–H functionalisation reactions under UV photolysis in flow and free from additives. Commercially available aldehydes are coupled to afford unsymmetrical aryl–alkyl and alkyl–alkyl ketones while mild conditions and lack of transition metal catalysts allow for exceptional functional group tolerance. Examples are given on small scale and in a larger scale continuous production.